CRITICAL PHENOMENOLOGY AND PHENOMENOLOGICAL CRITIQUE - POPA, Delia; REYNOLDS, Iaan (Studia Universitatis Babeș-Bolyai Philosophia, 2021)
Phenomenological critique attempts to retrieve the lived experience of a human community alienated from its truthful condition and immersed in historical crises brought by processes of objectification and estrangement. This introductory article challenges two methodological assumptions that are largely shared in North American Critical Phenomenology: the definition of phenomenology as a first person approach of experience and the rejection of transcendental eidetics. While reflecting on the importance of otherness and community for phenomenology’s critical orientation, we reconsider the importance of eidetics from the standpoint of Husserl’s genetic phenomenology, highlighting its historical and contingent character. Contrary to the received view of Husserl’s classical phenomenology as an idealistic and rigid undertaking, we show that his genetic phenomenology is interested in the material formation of meaning (Sinnbildung), offering resources for a phenomenological approach to a materialist social theory.